Parents with an unemployed adult child: Consumption, income, and savings effects - Kathryn Anne Edwards; Jeffrey B. Wenger (IZA Journal of Labor Economics, 2019)
The risk of labor market, health, and asset-value shocks comprise profound retirement savings challenges for older workers. Parents, however, may experience added risk if their children experience adverse labor market shocks. Prior research has shown that parents support their children financially through an unemployment spell. In this paper, we also provide evidence of financial support from parents and investigate if this financial support is accompanied by adjustments to parental consumption, income, or savings behavior. With longitudinal data on mothers and children from the Panel Study of Income Dynamics, we use within-mother variation in behavior to identify the effect of a child's labor market shock on parent outcomes. We find evidence of a decline in consumption, an increase in labor supply, and a decrease retirement savings, though the results are heterogenous among mothers. Our results point to aggregate inefficiencies and inequities that may result from family risk sharing.
Keywords: D64; J6; J20; D15; 330; Unemployment; intervivos transfers; retirement security; consumption; female labor supply